2007
DOI: 10.1063/1.2430522
|View full text |Cite
|
Sign up to set email alerts
|

Electronic absorption spectra of the protonated polyacetylenes HC2nH2+ (n=3,4) in the gas phase

Abstract: A new approach has been developed for the purpose of measuring the electronic transitions to bound exited states for cations that have been collisionally relaxed to low vibrational and rotational temperatures. This has been used to obtain the first gas phase electronic spectra of the protonated polyacetylenes using a two-color ion-photodissociation approach. Specifically, the origin bands in the B (1)A(1)<-- X(1)A(1) transitions of HC(6)H(2) (+) and HC(8)H(2) (+) (C(2v) geometry) were observed at 26,403.3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…This was achieved here with the cavity ringdown approach. However, the structure could still not be resolved and the same rotational profile as shown in Figure 3 in reference [9] was observed. Thus, it is concluded that the excited electronic state is short-lived as a result of lifetime broadening by intramolecular processes.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…This was achieved here with the cavity ringdown approach. However, the structure could still not be resolved and the same rotational profile as shown in Figure 3 in reference [9] was observed. Thus, it is concluded that the excited electronic state is short-lived as a result of lifetime broadening by intramolecular processes.…”
mentioning
confidence: 94%
“…An electronic transition of mass-selected C 6 H 3 ϩ could already be observed in the gas phase by using iontrapping technology [9]. However the possibility of laser power saturation in such experiments precluded a conclusion whether the excited-state structure was lifetime broadened or the resolution was just inadequate.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…24 A schematic of the current ion trapping apparatus is shown in Figure 3. In this approach 10 3 -10 4 buffer gas cooled ions are held in a radiofrequency (rf) trap where one tunable laser is used to search for the electronic transition of interest and a second fixed frequency laser of higher energy is used to fragment the electronically excited ions.…”
Section: A Carbon Chainsmentioning
confidence: 99%